Derecho penal y castigo. Una excusa para la protección de los derechos humanos en la sociedad del riesgo (2013)
The current trend in criminal law where human rights are used as an excuse to legitimize extreme security measures in response to the ¿danger¿ craze is examined in this paper. It is a trend that supports the legal basis for a kind of criminal law focused on public safety, one that facilitates criminal justice in different areas when it comes to pursuing ¿enemies,¿ which sometimes results directly in a violation of human rights, with the constant creation of rules that paradoxically also threaten those rights by virtue of the logic behind the punishment. The conclusion, based on these arguments, is that criminal guarantees or safeguards are weakened to the detriment of human rights, which are used either as tools to promote emancipation processes or as instruments to manipulate power and to justify barbaric acts stemming from an exaggeration of punitive power.